Pesticides Use Practice by Market Gardeners in Lome (Togo) - Aboudoulatif Diallo; Komi Zotchi; Povi Lawson-evi; Batomayena Bakoma; Essotolom Badjabaissi; Eklu-Gadegkeku Kwashie (Journal of Toxicology)
Pesticides are more and more used in African countries. The aim of this study is to evaluate the risk and the impact of pesticides on gardener’s health. It is a transversal descriptive study, which referred to vegetable growers, held in Lomé on the period from May 20 to June 5, 2017. Forty-eight (48) growers participated in the study. Men accounted for 70.8% of the study population against 29.2% of women. The level of education was primary (47.9%) in the majority of cases. Married people or couples represented 77.1% of cases. Most gardeners (72.9%) has no training in the use of pesticides. Pesticides were consistently applied (100%), including insecticides (72.7%), herbicides (9.1%), and fungicides (18.2%). Of 20 pesticides collected, 9 (45%) were approved by our authorities. Only 43.8% of growers were supplied with pesticides from authorized structures of agricultural products. Branches of plants (79.2%) were the spray means of most of the pesticides. Most gardeners (79, 2%) did not use personal protective equipment because of lack of resources for 81.6% of them. Water and environment contamination risk by pesticides was known by only 6.3% of gardeners. Among the adverse effects reported, pruritus was the majority in 85.4% of cases followed by headache (70.8%), cough (68.8%), and muscle pain (64.6%). The training of gardeners, monitoring and control of this informal sector, and the monitoring of unregistered pesticides will help to reduce the risk of poisoning of gardeners and consumers of vegetables as well as environmental pollution.